Implementasi Peraturan Ketenagakerjaan pada Hotel Berbintang di Bali - Ni Desak Made Santi Diwyarthi (UHN IGB Sugriwa Denpasar, 2018)
Tourism development brings implementation to the development of various components involved, both government, local communities, tourists and entrepreneurs in the tourism sector. This study seeks to understand the implementation of labor regulations in star-rated hotels in Bali. Quantitative research method with research instruments in the form of questionnaires, interview lists, checklists. The study population was the manager of star-rated hotels in Bali. The study sample were managers offour and five star hotels in Bali. The sampling method used was purposive random sampling. The results of the study show that employment agreements on starred hotels in Bali include agreements related to wages, agreements related to the operational functions of star-rated hotel management in Bali, agreements related to foreign workers and the use of outsourcing personnel, agreements related to occupational health and safety. The employment agreement also aims to maintain health and worksafety for its employees as follows: a. Protecting workers for their safety rights in doing work for the welfare of life and increasing national production and productivity. b. Ensure the safety of every other person at work. c. Production sources are maintained and used safely and efficiently